Nanocarrier functionalization strategies for targeted drug delivery in skin cancer therapy: current progress and upcoming challenges - Di Filippo, Leonardo Delello [UNESP]; de Paula, Mariana Carlomagno [UNESP]; Duarte, Jonatas Lobato [UNESP]; de Paula, Geanne Aparecida [UNESP]; Frigieri, Isadora [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2023)
Introduction: Skin cancer is the most common form of cancer worldwide, with increasing incidence rates in recent years. Although conventional chemotherapy and radiation therapy have been used for its treatment, these therapies have several limitations such as lack of selectivity and significant side effects. Targeted nanocarriers have emerged as a promising approach for the treatment of skin cancer. Areas covered: This review article provides an overview of targeted nanocarriers for skin cancer treatment. It covers the various types of targeted nanocarriers, including liposomes, polymeric nanoparticles, dendrimers, and inorganic nanoparticles. Expert opinion: There are still several challenges that need to be addressed before the clinical translation of targeted nanoparticles, such as optimization of their properties, development of reliable and robust characterization methods, and evaluation of their safety and efficacy in clinical trials. Another key aspect for the advancement of these studies is the need to improve regulatory aspects related to the toxicity and regulation of nanomedicines targeting skin cancer. Overall, targeted nanocarriers hold great potential for the development of safe and effective treatments for skin cancer, which can contribute to a better prognosis and overall patients’ life quality.
Keywords: controlled release; melanoma; Nanoparticles; surface modification; target delivery